2018
DOI: 10.4085/1062-6050-313-16
|View full text |Cite
|
Sign up to set email alerts
|

Decision to Return to Sport After Anterior Cruciate Ligament Reconstruction, Part I: A Qualitative Investigation of Psychosocial Factors

Abstract: Context:  Return-to-sport criteria after anterior cruciate ligament (ACL) injury are often based on “satisfactory” functional and patient-reported outcomes. However, an individual's decision to return to sport is likely multifactorial; psychological and physical readiness to return may not be synonymous. Objective:  To determine the psychosocial factors that influence the decision to return to sport in athletes 1 year post–AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 54 publications
3
78
1
2
Order By: Relevance
“…Also, psychological aspects are not taken into account. Recent studies have shown an influence of psychological parameters on performance and progress for return to sport [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Also, psychological aspects are not taken into account. Recent studies have shown an influence of psychological parameters on performance and progress for return to sport [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Among both groups, it is apparent that numerous participants perceived they were experiencing suboptimal knee health despite a relatively high level of functional capacity as demonstrated by performance testing. Based on the responses to the PROs and the qualitative portion of this study, 44 patients appeared to experience subjective functional changes, heightened awareness, changing expectations and assumptions, and a general ''coming to terms'' with their ACL injuries. This overall process may result in individuals defining a ''new normal'' for knee function.…”
Section: Self-reported Outcomesmentioning
confidence: 95%
“…This hesitancy may be a clinical expression of the theme of hesitation and lack of confidence led to self-limiting tendencies identified during the qualitative portion of this investigation. 44 Whereas the dynamic functional performance values exceeded the normal limb symmetry considered acceptable for sport activity, the hesitancy expressed by participants may support the continued use of single-legged-hop assessments during late-stage rehabilitation to regain patient confidence and facilitate the transition to return to sport.…”
Section: Functional Performance Testingmentioning
confidence: 97%
“…3,48 Además del temor a una nueva lesión, distintos autores muestran factores como la falta de confianza, la inseguridad, la motivación y un cambio en las prioridades y en las expectativas como aspectos primordiales que explican la conducta postoperatoria ante la actividad deportiva. 3, [49][50][51] Ese último punto, que vale la pena ser considerado antes de analizar fríamente las tasas de retorno deportivo, se refleja claramente en nuestro estudio en un significativo grupo de 34 pacientes (26%), que simplemente no retornaron al deporte en el periodo estudiado por motivos no relacionados a su cirugía, ni a su rodilla.…”
Section: Descripción Resultadosunclassified